A prospective study on the attitude of post graduates in general pediatrics toward pediatric oncology subspeciality as a career - Ram Prakash Thirugnanasambandam; Magatha Sneha Latha; Aravind Moorthy; Lakshminarayanan Kannan; Venkataraman Paramasivam; Julius Xavier Scott (Indian Journal of Medical and Paediatric Oncology)
Objectives: The health care scenario in India is experiencing an increase in the number of children affected with cancer and the number of pediatric oncologists available to treat these children are few and the awareness of childhood cancer is decimally low. Hence, the purpose of this study was to determine the attitude of post-graduate students of general pediatrics towards childhood cancer and to assess their interest in pursuing pediatric oncology as a specialty in their carrier. Materials and Methods: The study was conducted among 188 post-graduates hailing from various Medical colleges all over South India who were attending a 2 day workshop at Chennai. The survey was a 10 point questionnaire pertaining to their previous training, competence, interest toward the field of hematooncology. The data were analyzed by SPSS 18.V software. Results: Among the post-graduates, 74.7% of them reported that they did not have a pediatric oncology unit in their institution. 63.3% reported that they never been posted in pediatric oncology clinical postings before. 62% were not interested in pursuing pediatric oncology as a sub-specialty at all. 45.3% felt that pediatric oncology was too depressing to take as a specialty. 46.7% felt that late diagnosis and referral was the main factor which contributed to the failure of effective treatment of childhood cancers. 52.7% had never attended a class on pediatric oncology. 61.3% felt that they did not have sufficient knowledge to suspect and refer a child with cancer. 92% felt that there was a need to improve pediatric oncology teaching in their curriculum. 56.7% felt that the best way to imprint awareness on childhood malignancies was to improve pediatric oncology teaching in their medical curriculum. Conclusion: The results show that majority of post-graduates in pediatrics were not interested in pursuing pediatric oncology as a sub-specialty. The main reasons may be lack of specialized Pediatric oncology units in the majority of the medical institutions, lack of opportunity of these post-graduates to attend clinical postings and theory classes. They thus lack sufficient information in this field and hence do not want to take up a career in pediatric oncology.